Cell-Free DNA: An Underestimated Source of Antibiotic Resistance Gene Dissemination at the Interface Between Human Activities and Downstream Environments in the Context of Wastewater Reuse - Woegerbauer, Markus; Bellanger, Xavier; Merlin, Christophe (Frontiers in Microbiology, 2020)
Reducing the dissemination of antimicrobial resistance (AMR) is one of the biggest challenges for public health today. Containment of AMR is compromised by AMR determinants of anthropogenic origin that are continually released into the environment via human waste streams from animal husbandry, food production facilities and reclaimed or untreated wastewater in the form of resistant bacteria or as antimicrobial resistance genes (ARGs) encoded on free extracellular DNA (exDNA) or encapsulated in vesicles or bacteriophages. Although much effort has been devoted into the elucidation of cell-associated propagation of AMR substantial knowledge gaps on the role of cellfree DNA in horizontal gene transfer in wastewater and downstream environments remain. The contribution of cell-free DNA to the overall spread of AMR has been underestimated for a long period of time. The increasing water scarcity associated to climatic change requires developing innovative wastewater reuse practices and, concomitantly, a robust evaluation of AMR occurrence by implementing treatment technologies able to exert a stringent control on AMR propagation in downstream environments exposed to treated or non-treated wastewater. This necessarily implies understanding the fate of ARGs on various forms of cell-free DNA, and during treatment processes that are permissive to their formation. We propose that comprehensive approaches, investigating both the occurrence of ARGs and their compartmentalization in different forms of cellular or cell-free associated DNA should be established for each treatment technology. This should then allow